Phronetic Leadership and Public Values of Elected Local Government Officials: Its Implications for Ethical and Moral Standards - Soriano, Imelda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2026)
In an era where effective governance demands more than administrative acumen, this study investigates the pivotal role of phronetic leadership in fostering ethical and moral standards among elected local government officials in Zambales, Philippines. Phronetic leadership emerged as a crucial paradigm, emphasizing the cultivation of practical wisdom in decision-making processes. This study explored the relationship between phronetic leadership and public values among elected local government officials in Zambales, Philippines, to enhance ethical and moral standards in governance. Employing a descriptive-correlational research design with 156 respondents, the researchers used a structured questionnaire to analyze phronetic leadership and public values among local government officials. Descriptive and inferential statistics were used to analyze the collected data using SPSS 29. Findings revealed that elected local government officials consistently practice creating shared context, communicating the essence and equity and fairness, while grasping the essence, exercising political power, and fostering political wisdom; they also face challenges in maintaining moral clarity under pressure and in promoting structural equity. Although public values such as justice and service orientation were strongly upheld in practice, weak correlations were found between individual phronetic leadership traits and specific governance outcomes. The analysis showed that leadership traits alone did not strongly influence public values in governance. This means that a more complete approach to governance is needed. This approach should focus on ethical leadership but also include support from institutions, citizen involvement, and the ability to respond to complex social and political issues.